1990
DOI: 10.1007/bf00003399
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate-2-sulfate as a dietary vitamin C source for Atlantic salmon (Salmo salar): 2. Effects of dietary levels and immunization on the metabolism of trace elements

Abstract: Atlantic salmon fingerlings were fed a vitamin C deficient diet for four months. The fish were then provided a dry, practical fishmeal based diet supplemented with 0, 500 or 5000 mg vitamin C/kg as L-ascorbic acid or equivalent amounts of ascorbate-2-sulfate. After six weeks on these diets ten fish in each group were injected with a soluble antigen (NIP11-LPH). Six weeks thereafter blood, liver, kidney, spleen and vertebrae were examined for trace elements. The livers were also analysed for metallothionein.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…36 The detailed action mechanism is that lysosomal autophagy catabolize excess ferritin into end-state hemosiderin complexes, however, AA can inhibit this process and block the degradation of cytoplasmic ferritin, and nally keep the iron stored in the body as ferritin-bound iron. 37,38 In our study, a higher level of AAS can be found in the CR group, which means CR group have higher level of AA and leading to higher level of ferritin-bound iron be stored and used, which is consistent with the reported literatures. Oleamide, as one of the two identied biomarkers, is the amide of oleic acid, and is synthesized from oleic acid and ammonia by enzymatic amidation, and previous study showed that oleamide has high anti-inammatory activity.…”
Section: Discussionsupporting
confidence: 82%
“…36 The detailed action mechanism is that lysosomal autophagy catabolize excess ferritin into end-state hemosiderin complexes, however, AA can inhibit this process and block the degradation of cytoplasmic ferritin, and nally keep the iron stored in the body as ferritin-bound iron. 37,38 In our study, a higher level of AAS can be found in the CR group, which means CR group have higher level of AA and leading to higher level of ferritin-bound iron be stored and used, which is consistent with the reported literatures. Oleamide, as one of the two identied biomarkers, is the amide of oleic acid, and is synthesized from oleic acid and ammonia by enzymatic amidation, and previous study showed that oleamide has high anti-inammatory activity.…”
Section: Discussionsupporting
confidence: 82%
“…Decreased ironbinding capacity in vitamin C-deficient rainbow trout was reported by Blazer (1982), and serum iron constituted only 3 -7% of the iron-binding capacity in all groups (Blazer 1982). The decreased ironbinding capacity in vitamin C-deficient fish may therefore be due to malfunctions in the iron transport as have been suggested by Maage et al (1990), rather than a depression of a nonspecific resistance factor. Dabrowski et al (1990) found only minor effects of AA and ascorbate-2-sulfate on iron metabolism in rainbow trout.…”
Section: Discussionmentioning
confidence: 95%
“…Ascorbate has been shown to influence the absorption and utilization of iron in fish (Sandnes et al 1984;Maage et al 1990), and anemia has been reported in AA deficient fish (Hilton 1984;Sandnes et al 1990). The total serum iron concentration was significantly (p < 0.005) correlated to the liver AA concentration in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that AA deficiency causes anemia in fish (Hilton et al 1978;Halver et al 1975;Waagbo et al 1989), but the present study also reveals a reduction in blood haemoglobin and the number, size and haemoglobin content of circulating erythrocytes caused by immunization. These findings initiated further studies on the metabolism of trace elements related to immunological aspects of dietary AA and AS in fish as reported by MAge et al (1990).…”
Section: Antibody Productionmentioning
confidence: 99%